2019
DOI: 10.1002/adma.201901417
|View full text |Cite
|
Sign up to set email alerts
|

Lossless Fast Drop Self‐Transport on Anisotropic Omniphobic Surfaces: Origin and Elimination of Microscopic Liquid Residue

Abstract: Surfaces enabling directional drop self‐transport have exceptional applications in digital microfluidics, chemical analysis, bioassay, and microreactor technology. While such properties have been obtained by engineering a surface with anisotropic microstructures, a microscopic liquid residue—though it might be invisible macroscopically—is generally left behind the transported drop, resulting in undesired transport loss and severely limiting practical applications of the surface. Here, the origin of microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…[24] The alkylsilane, featuring a much less mobile CCC skeleton (bond angle = 109 o ) than that of SiOSi, can be considered as a conventional rigid layer when grafted on the surface (Figure 1D,E). [21,36] In contrary to GQLS, GRS shows much higher CAHs to highly wetting liquids (Figure 1F and Figure S4, Supporting Information). For example, the CAH of Krytox101, FC40, and FC72 presented on GRS is 2.7 o , 4.5 o , and 0.8 o , while that on GQLS is 0.5 o , 0.4 o , and 0.2 o , respectively (Tables S1 and S2, Supporting Information).…”
Section: Fabricate Gradient Quasi-liquid Surface For Self-propulsion Of Highly Wetting Liquidsmentioning
confidence: 98%
“…[24] The alkylsilane, featuring a much less mobile CCC skeleton (bond angle = 109 o ) than that of SiOSi, can be considered as a conventional rigid layer when grafted on the surface (Figure 1D,E). [21,36] In contrary to GQLS, GRS shows much higher CAHs to highly wetting liquids (Figure 1F and Figure S4, Supporting Information). For example, the CAH of Krytox101, FC40, and FC72 presented on GRS is 2.7 o , 4.5 o , and 0.8 o , while that on GQLS is 0.5 o , 0.4 o , and 0.2 o , respectively (Tables S1 and S2, Supporting Information).…”
Section: Fabricate Gradient Quasi-liquid Surface For Self-propulsion Of Highly Wetting Liquidsmentioning
confidence: 98%
“…In 2019, Huang et al 77 carried out an extended investigation on the formation mechanism of microscopic liquid residues on similar re-entrant proles. They revealed that the liquid residue is governed by a dynamic wetting process rather than simply the contact angle hysteresis of the surface.…”
Section: Re-entrant Micropatternsmentioning
confidence: 99%
“…8c). 77 The analyte droplets spontaneously moved toward the center where the two droplets merged, and a microscope above the setup was used to monitor the reaction.…”
Section: Applicationsmentioning
confidence: 99%
“…Droplet movement was studied on microstripes constructed on silicon wafer substrates. 51 The patterned surfaces were grafted with liquid-like perfluoropolyether brushes to eliminate microscopic liquid residue that is typically left by moving drops. The resulting behavior was termed 'lossless fast drop transport'.…”
Section: Liquid-like Surfacesmentioning
confidence: 99%